1985
DOI: 10.1523/jneurosci.05-01-00181.1985
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic responses of spinal neurons in locus coeruleus-spinal cord co-cultures

Abstract: Locus coeruleus (LC) explants were co-cultured with dissociated spinal neurons of mice. Nerve fibers exhibiting catecholamine fluorescence radiated from the explants and frequently invested spinal cord (SC) neurons close to the explants. Electrical stimulation of the explant and iontophoretic application of norepinephrine evoked a spectrum of slow depolarizing, hyperpolarizing, and biphasic responses in the SC cells. The responses to LC stimulation and to application of norepinephrine were usually similar in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Hyperpolarizing inhibitory responses to iontophoresed NE have been reported in many CNS areas, including spinal motoneurons (Phillis et al, 1968;Weight and Salmoiraghi, 1967) and spinal cord explants (Pun et al, 1985), although the specificity of the motoneuron response has been questioned (Engberg et al, 1976). We also sometimes observed early hyperpolarizations after LL region stimulation and, in hyperinnervated motoneurons, a lower membrane potential.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Hyperpolarizing inhibitory responses to iontophoresed NE have been reported in many CNS areas, including spinal motoneurons (Phillis et al, 1968;Weight and Salmoiraghi, 1967) and spinal cord explants (Pun et al, 1985), although the specificity of the motoneuron response has been questioned (Engberg et al, 1976). We also sometimes observed early hyperpolarizations after LL region stimulation and, in hyperinnervated motoneurons, a lower membrane potential.…”
Section: Discussionmentioning
confidence: 58%
“…In locus coeruleus-spinal cord cocultures, Pun et al (1985) observed an alpha-adrenergic-mediated depolarization following NE iontophoresis or stimulation of the LC. The depolarization was sometimes preceded by a hyperpolarization similar to the biphasic responses we observed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…By contrast, in this study in freely moving cats, applied NE had no excitatory effect on tonic GG muscle activity, but significantly reduced GG muscle activity during both W and light SWS. Other studies have also shown that NE is not always excitatory, but can also cause hyperpolarization and hence suppression of motoneuron activity (Pun et al, 1985;Vornov and Sutin, 1986). It seems likely that this depressant effect of NE may be mediated by a 2 -adrenoceptors located on HMN.…”
Section: Ne and Gg Muscle Activitymentioning
confidence: 92%
“…Alpha receptormediated excitation of the spinal cord neurons by stimulating the LC and NA has been observed in LC-spinal cord cocultures (Pun et al, 1985). These findings imply that the a,-adrenergic receptor mediates activation of the spinal neurons.…”
Section: Previously Dementioning
confidence: 76%